Active vibration control development in ultra‐precision machining. (April 2021) - Aggogeri, Francesco; Merlo, Angelo; Pellegrini, Nicola
This study presents a combined feedback–feedforward adaptive regulator applied to an active vibration control tool holder platform to contain the effect of machining vibrations. The proposed mechatronic solution can be integrated in a milling machine tool as an interface between the beam ( Z -axis) and the tool holder. The aim is to counteract vibrations in the broadband frequency range (100 Hz–900 Hz), controlling the tool position in real time. The active vibration control system is based on the harmonic steady-state concept due to the sinusoidal representation of the disturbance signals. The study focuses on the regulator architecture and the main logics applied to satisfy the required performance. A full investigation is executed through simulations and experimental campaigns, proving the disturbance reduction. The active vibration control system is implemented on a 4-axis machine tool and validated using multitonal disturbances. The system is evaluated in compensating a set of undesired effects, such as vibrations generated by unbalanced tools or hard material cutting processes. The obtained results show a maximum reduction of the vibration amplitude by 43.7% at the critical frequency.